2010
DOI: 10.1093/socrel/srq005
|View full text |Cite
|
Sign up to set email alerts
|

Age, Period, and Cohort Effects on U.S. Religious Service Attendance: The Declining Impact of Sex, Southern Residence, and Catholic Affiliation

Abstract: I use repeated, cross-sectional data from 1972 to 2006 to analyze age, period, and cohort effects on Americans' frequency of religious service attendance with cross-classified, random-effects models. The results show that the frequency of religious service attendance is relatively stable, with a modest period-based decline in the 1990s and little overall cohort effect. Although aggregate rates of attendance are stable, there are large changes across cohorts and periods in differences in attendance between men … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 28 publications
2
59
1
Order By: Relevance
“…Other studies (Piontek et al, 2012;Schwadel, 2010) similarly use the HAPC model to find period and cohort trends which may be over-interpretations of their data.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies (Piontek et al, 2012;Schwadel, 2010) similarly use the HAPC model to find period and cohort trends which may be over-interpretations of their data.…”
Section: Discussionmentioning
confidence: 99%
“…Religion has not escaped attention (Voas and Crockett 2005;Wolf 2008;Schwadel 2010aSchwadel , 2010bSchwadel , 2011Schwadel , 2013 We proceed in three steps, beginning with graphical examination of the data.…”
Section: The General Social Survey In the United States Is Run By Thementioning
confidence: 99%
“…Ploch and Hastings (1994) came down on the side of age rather than cohort effects, while Miller and Nakamura (1996) supported the idea of generational change, although they saw it as a one-time shift associated with the 1960s rather than a gradual and continuing decline. Presser and Chaves (2007) also suggested that change may be discontinuous, based on an absence of any overall trend in church attendance between 1990. Schwadel (2010a asserted that frequency of attendance was shaped by strong positive age effects, modest period decline in the 1990s, and no substantial cohort differences.…”
mentioning
confidence: 99%
“…Glenn (2005, p. 6) This paper considers one of these solutions, proposed recently by Yang and Land (2006) with some additional methodological caveats discussed in subsequent papers (Frenk, Yang and Land 2013;Yang 2006;. The methodology has already been employed in a number of empirical applications, studying social trends in happiness (Yang 2008a), voter turnout (Dassonneville 2013), obesity (Reither, Hauser and Yang 2009), religious service attendance (Schwadel 2010), and cannabis use (Piontek et al 2012), to name a few. With the relatively speedy uptake of this method, understanding how and when it works is of profound importance.…”
Section: Introductionmentioning
confidence: 99%